Incidence, Diagnosis, and Outcomes of Vocal Fold Immobility After Esophageal Atresia (EA) and/or Tracheoesophageal Fistula (TEF) Repair - Mortellaro, V. E.; Pettiford, J. N.; St Peter, S. D.; Fraser, J. D.; Ho, B.; Wei, J. (European Journal of Pediatric Surgery, 2011)
The diagnosis of vocal fold paralysis in an infant is a devastating finding that may require a permanent tracheotomy. The incidence of congenital vocal fold paralysis is unknown, but it is thought to be more common in infants with anatomic anomalies in the aero-digestive system. Vocal fold paralysis after surgical repair of esophageal atresia and tracheoesophageal fistula is a rare finding often diagnosed after multiple failed extubations. Currently infants do not routinely undergo documentation of vocal fold motion prior to esophageal atresia repair. We report here on our experience with this rare complication.A retrospective review was done of patients with esophageal atresia and/or tracheoesophageal fistula from 1985 to 2009. Patient demographics, operative techniques, and outcomes were collected.150 patients were identified. Mean age at surgical intervention was 12±33 days. Otolaryngology service was consulted for 13% of patients with postoperative failure. Awake fiberoptic laryngoscopy identified 3% of patients with vocal fold paralysis. Bilateral vocal fold paralysis was found in 3 patients, and 2 patients had unilateral vocal fold paralysis. Patients with bilateral paralysis were treated with tracheotomy; unilateral paralysis was treated expectantly.In this study, 3% of patients were diagnosed with vocal fold paralysis after esophageal atresia repair. The etiology of vocal fold paralysis in this study is difficult to assess. Preoperative fiberoptic laryngoscopy is recommended to identify children with congenital vocal fold paralysis prior to surgical intervention, especially in those requiring revision surgery.
Keywords: esophageal atresia; vocal cord paralysis; bronchoscopy